2015
DOI: 10.1007/s00270-015-1208-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Liver Tumors with Lipiodol TACE: Technical Recommendations from Experts Opinion

Abstract: Transarterial chemoembolization with Lipiodol (Lipiodol TACE), also called conventional TACE, was developed in the early 1980s and widely adopted worldwide after randomized control trials and meta-analysis demonstrated superiority of Lipiodol TACE to best supportive care. Presently, there is no level one evidence that other TACE techniques are superior to Lipiodol TACE for intermediate stage hepatocellular carcinoma (HCC), which includes patients with preserved liver function and nonsurgical large or multinodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
174
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(177 citation statements)
references
References 83 publications
1
174
2
Order By: Relevance
“…9,20 Theoretically, the rate of complications should be higher in the combined TACE and RFA than that of TACE or RFA monotherapy. 38 However, the common procedure-related complications of the combined therapy such as hepatic infarction, biloma, abscess and hepatic arterial bleeding, reported by others, 27,31,34,39 did not occur in our study. In our study, posttreatment syndrome and transient increase in liver enzymes slightly were observed in all patients within 1 week after the treatment, which were comparable with those reported in other studies [8][9][10][11] ; these symptoms were usually self-limited and reversible without special treatment.…”
Section: Discussioncontrasting
confidence: 41%
“…9,20 Theoretically, the rate of complications should be higher in the combined TACE and RFA than that of TACE or RFA monotherapy. 38 However, the common procedure-related complications of the combined therapy such as hepatic infarction, biloma, abscess and hepatic arterial bleeding, reported by others, 27,31,34,39 did not occur in our study. In our study, posttreatment syndrome and transient increase in liver enzymes slightly were observed in all patients within 1 week after the treatment, which were comparable with those reported in other studies [8][9][10][11] ; these symptoms were usually self-limited and reversible without special treatment.…”
Section: Discussioncontrasting
confidence: 41%
“…The dose in milliliters of ethiodized oil used for a single conventional transarterial chemoembolization session is approximately equal to the sum of the target tumor diameters in centimeters (8). The reported maximum dose of ethiodized oil per session is 10 mL (8,47) or 15 mL (48). The endpoint of conventional transarterial chemoembolization is the occlusion of tumor feeders and disappearance of staining of target tumors on digital subtraction angiography.…”
Section: Techniques Of Superselective Conventional Transarterial Chemmentioning
confidence: 98%
“…No whole liver cTACE was performed. An emulsion containing up to 50 mg doxorubicin (Adriamycin, Zhejiang HISUN Pharmaceutical Co. Ltd., Taizhou, China) and 2–20 ml Lipiodol (Lipiodol Ultra-Fluide, Laboratoire Guerbet, Aulnay-sous-Bois, France) was infused, followed by bland embolization with 100–300 µm polyvinyl alcohol particles (Cook Medical Inc., Bloomington, USA) until arterial inflow was substantially reduced as seen on fluoroscopy [1, 8, 19]. In all cases, either a selective or a super-selective approach was chosen.…”
Section: Methodsmentioning
confidence: 99%